Rethinking our Work with Leaders: Using Developmental Threshold Zones in Coaching. Issue 4 (3rd March 2021) - Drake, David B.
Abstract : The current paper brings together three bodies of work, each of which contributes to a new approach to learning and development, and identifies three elements that can be used with leaders in coaching: security, stories, and scaffolding. In particular, it looks at how Developmental Threshold Zones (Drake, 2018a) can be used to enrich the coaching process and outcomes with leaders. The first section explores attachment theory and its contribution to understanding how leaders secure themselves relationally. The second section explores narrative coaching and its contribution to understanding how leaders develop and move through change. The third section explores Vygotsky's (1934/1987, 1978) work on zones of proximal development and its contribution to our understanding of the scaffolding leaders need into order to grow. Each section contributes to the our understanding of how to use Developmental Threshold Zones (DTZs) and how it can be used in coaching to facilitate transformative experiences for leaders using their own stories.